The Sao Mateus–Jabaquara Trolleybusway Concession in Brazil - Rebelo, Jorge (World Bank, Washington, DC, 2015)
The authors describe how Sao Paulo State granted a 20-year concession for operating a busway, one requirement for which was that the concessionaire replace the diesel bus operation with electric traction (trolleys). This was not a "greenfield concession" but is probably the only "busway" concession undertaken so far worldwide. With roughly 16,000 buses fighting their way through heavy traffic under traffic policies geared to automobiles, bus services was slow and unreliable. Then Sao Paulo adopted certain practices aimed at improving bus operations. Between 1983 and 1987, it implemented a segregated trolleybus corridor between Sao Mateus and Jabaquara, to be opened as a private concession regulated by the state of Sao Paulo. The concession was to operate for 20 years but the winning consortium had to invest in only part of the equipment, because part of it was in place. This made things less risky for the private consortium and allowed the state to complete an environmentally friendly project with the help of the private sector. The concession has so far been a success - an example to be followed. After an initial increase, demand for the busway began to fall in 1998 and 1999. This was part of a general decline in demand for the bus system because of: a) A drop in jobs resulting from the economic slowdown. b) A growth in the use of automobiles. c) Competition from illegal buses (vans), which offer door-to-door service. The state was late in completing the aerial network for the trolleyway and rehabilitating sections of the roadway. This delayed replacement of diesel buses by trolleybuses. State representatives indicated it might be better in future to find a mechanism through which the concessionaire instead of the state would undertake infrastructure works and would also handle administration of integration terminals.